An Analysis of Modulation Technique in the Translation of Bumi Manusia Novel into this earth of Mankind - Mohammad Yahya; Syifa Aullianisa Fatiha; Danny Gandana Nugraha (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2021)
The translation is concerned with the equivalence between the source text and target text. Achieving the equivalence is challenging due to the differences in terms of grammar, culture, and pragmatics. One technique to meet the aspect of naturalness is by using modulation techniques. Therefore, this study aims to investigate the types of modulation used in translating the Indonesian novel “Bumi Manusia” into English “This Earth of Mankind” and compare the use of obligatory and optional in the application of modulation. The method used in this study was a qualitative one that applied modulation techniques in analyzing 80 data found in the novels. The results show that the type commonly found is active for passive with 38 cases (47.5%). The application of optional modulation is 68 times (85%) and obligatory modulation is 12 times (15%).